Anti-tumor effects of metformin in animal models of hepatocellular carcinoma: a systematic review and meta-analysis. - Juan Li; Pratika Y Hernanda; Wichor M Bramer; Maikel P Peppelenbosch; Judith van Luijk; Qiuwei Pan (PLoS ONE, 2015)
Background Several studies have reported that metformin can reduce the risk of hepatocellular carcinoma (HCC) in diabetes patients. However, the direct anti-HCC effects of metformin have hardly been studied in patients, but have been extensively investigated in animal models of HCC. We therefore performed a systematic review and meta-analysis of animal studies evaluating the effects of metformin on HCC. Methods We collected the relevant studies by searching EMBASE, Medline (OvidSP), Web of Science, Scopus, PubMed Publisher, and Google Scholar. Studies were included according to the following inclusion criteria: HCC, animal study, and metformin intervention. Study quality was assessed using SYRCLE's risk of bias tool. A meta-analysis was performed for the outcome measures: tumor growth (tumor volume, weight and size), tumor number and incidence. Results The search resulted in 573 references, of which 13 could be included in the review and 12 included in the meta-analysis. The study characteristics of the included studies varied considerably. Two studies used rats, while the others used mice. Only one study used female animals, nine used male, and three studies didn't mention the gender of animals in their experiments. The quality of the included studies was low to moderate based on the assessment of their risk of bias. The meta-analysis showed that metformin significantly inhibited the growth of HCC tumour (SMD -2.20[-2.96,-1.43]; n=16), but no significant effect on the number of tumors (SMD-1.05[-2.13,0.03]; n=5) or the incidence of HCC was observed (RR 0.62[0.33,1.16]; n=6). To investigate the potential sources of significant heterogeneities found in outcome of tumor growth (I2=81%), subgroup analyses of scales of growth measures and of types of animal models used were performed. Conclusion Metformin appears to have a direct anti-HCC effect in animal models. Although the intrinsic limitations of animal studies, this systematic review could provide an important reference for future preclinical animal trials of good quality and clinical development.